Edukasi Perbaikan Kualitas Lingkungan Pemukiman di Kelurahan Mata Air, Padang Selatan, Kota Padang - Azyyati Ridha Alfian; Rd Aldifa Taufiqurrahman; Mutia Rahma Zuwinda; Reviana Denisa Hartanti; Salwa Cintia; Shafira Ananda; Zavina Fathya Azizqi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Environmental health is an ecological balance that must exist between humans and the environment to ensure human health. Environmental sanitation of settlements is all efforts to improve and maintain the health of settlements and their environment and their effects on humans. Various environmental health problems in Kelurahan Mata Air in South Padang sub-district, Padang City, especially in RT 2/RW 11, include the disposal of community latrines directly into the river, not having a septic tank, and also many people who throw garbage into the river. This activity aims to increase public knowledge about healthy latrines, homes, and residential environments. The method used was providing counselling which is carried out using a lecture and video approach. The results of the activity obtained an increase in community knowledge by 45% compared to before being given counselling/education as measured by a questionnaire technique using a pre-post activity questionnaire during one day the activity took place. The community was very enthusiastic about listening to the counselling delivered. The interest and willingness of the community to improve the quality of the residential environment and change their habits can worsen their environmental conditions, which was very high, is reflected in the community's commitment to the sustainability of the following environmental improvement program, which will be continued by collaboration between the community service team and community to improve the quality of the residential environment.